Meningkatkan Pemahaman Tentang Larangan Perundungan Melalui Media Ular Tangga: Perspektif Agama Islam Pada Siswa Kelas IV SDN 036 Ujung Berung - Anggi Rostiani Nurjanah; Dian Salsabila; Isabella Putri Shufania; Nadya Zulfi Soleha; Siti Hardianti Fitri; Asep Rudi Nurjaman (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
In the view of the Islamic religion, bullying is an action that is inappropriate for every community to carry out because it has a negative impact on life. However, in reality, people still carry out these actions even though this prohibition has been explained in the Islamic religion. Bullying that is often encountered includes physical bullying, verbal bullying, relational bullying, and cyber bullying. Bullying in any form has a negative impact on both the victim and the perpetrator, the victim can experience mental problems such as anxiety disorders while the perpetrator can also experience emotional disorders. Therefore, this research was carried out to develop learning media in the form of "Snakes and Ladders" which aims to increase understanding of the prohibition of bullying from an Islamic religious perspective for class IV students at SDN 036 Ujung Berung. The research method used in this research is the mix method by adopting the ADDIE model. The results of the research show that the use of snakes and ladders media is effective in increasing students' understanding of the prohibition of bullying in Islam, as evidenced by the average score obtained from students is 86.94, with a minimum score of 77.78 and a maximum score of 100. A standard deviation of 6.60 indicates the level variation in student assessments, while the variance of 43.51 indicates how far the data is spread from the average.